SISTEM INFORMASI GEOGRAFIS PEMETAAN LETAK BARBERSHOP PADA KOTA BATURAJA - Isnania, Affini Salsabilla; Purnama Sari, Arini; Bila, Firwinca; Utruja, Nur Alifahtul; Pujianto (Universitas Methodist Indonesia, 2025)
Barbershop is a men-only barbershop that has spread in the corners of the city. Barbershop is an option for young people from adolescence to adulthood because barbershop provides more services that cannot be obtained in conventional barbershops. With the high interest of visitors and the need for barbershops, often the search for barbershops becomes an obstacle for visitors because they do not know the location of the barbershop they want, especially to find a barbershop in Baturaja is not easy for visitors from outside the area because of the many barbershops that are in the scope of Baturaja, therefore for the search for barbershopsin Baturaja a Geographic Information System is needed that can make it easier to know the location and distance of barbershops. In designing and building a Geographic Information System, map data is needed in the form of location coordinates by observation at each barbershop. Geographic Information System using Google Maps Application as a map of the region, this system is lighter and easier to use because it only focuses on the location and proximity of barbershop. With the Geographic Information System visitors who come in Baturaja will be helped to find the location of the nearest barbershop.